Single-cell RNA sequencing reveals a new mechanism of endothelial cell heterogeneity and healing in diabetic foot ulcers - Songyun Zhao; Hua Yu; Zihao Li; Wanying Chen; Kaibo Liu; Hao Dai; Gaoyi Wang; Zibing Zhang; Jiaheng Xie; Yucang He; Liqun Li (Biology Direct)
Abstract Diabetic foot ulcers (DFU) are a common and severe complication among diabetic patients, posing a significant burden on patients’ quality of life and healthcare systems due to their high incidence, amputation rates, and mortality. This study utilized single-cell RNA sequencing technology to deeply analyze the cellular heterogeneity of the skin on the feet ofDFU patients and the transcriptomic characteristics of endothelial cells, aiming to identify key cell populations and genes associated with the healing and progression of DFU. The study found that endothelial cells from DFU patients exhibited significant transcriptomic differences under various conditions, particularly in signaling pathways related to inflammatory responses and angiogenesis. Through trajectory analysis and cell communication research, we revealed the key role of endothelial cell subsets in the development of DFU and identified multiple important gene modules associated with the progression of DFU. Notably, the promoting effect of the SH3BGRL3 gene on endothelial cell proliferation, migration, and angiogenic capabilities under high glucose conditions was experimentally verified, providing a new potential target and theoretical basis for the treatment of DFU. This study not only enhances the understanding of the pathogenesis ofDFU but also provides a scientific basis for the development ofnew therapeutic strategies.